The effect of lecithin supplementation on plasma choline concentrations during a marathon - Buchman, A. L.; Awal, M.; Jenden, D.; Roch, M.; Kang, S. H. (Journal of the American College of Nutrition, 2000)
BACKGROUND: Previous studies have shown that plasma and urinary free choline concentrations decrease significantly during a marathon, and that these decreases may be associated with decreased performance. OBJECTIVE: In a pilot study, we sought to determine whether lecithin supplementation prior to a marathon would maintain plasma free and urinary choline concentrations and improve performance versus placebo. METHODS: 12 accomplished marathon runners, males (7) and females (5), 21 to 50 years of age were randomized to receive lecithin (4 capsules BID; PhosChol 900) or placebo beginning one day prior to the 2000 Houston-Methodist Health Care Marathon. The lecithin supplement provided approximately 1.1 g of choline on a daily basis (2.2 g total). Runners estimated finish time based on recent performance and training. Fasting, pre- and post-marathon plasma and a five-hour urine collection were analyzed for free choline and plasma for phospholipid-bound choline. Pre-race predicted, as well as the actual finish time, were recorded. RESULTS: All subjects completed the marathon. Plasma free choline decreased significantly in the placebo group and increased significantly in the lecithin group (9.6 +/- 3.6 to 7.0 +/- 3.6 nmol/mL vs. 8.0 +/- 1.2 to 11.7 +/- 3.6 nmol/mL, p = 0.001 for the delta between groups). No significant changes in plasma phospholipid-bound choline concentration were observed. There was a non-significant decrease in urine free choline in both groups. Actual finish time was 256.3 +/- 46.3 minutes for the lecithin group vs. 240.8 +/- 62.0 for the placebo group and the actual:predicted time was 1.03 +/- 0.06 (lecithin) and 1.07 +/- 0.08 (placebo), p = 0.36. CONCLUSION: Short-term lecithin supplementation prior to a marathon maintains normal plasma free choline concentration during the race, but failed to improve performance.